Theoretical analysis and mathematical modelling of a high-pressure pump in the common rail injection system for diesel engines. (February 2015) - Qian, Dexing; Liao, Ridong
In this paper, a study on the performance of a high-pressure pump of the common rail fuel injection system is presented. The mathematical models established include: (i) the fluid model for the pump chamber and rail which takes the structural deformation and interface leakage into consideration; (ii) the nonisothermal fluid–structure interaction model for the leakage at the piston/cylinder interface; and (iii) the unified model for the physical properties of the fuel such as dynamic viscosity, density and isobaric specific heat capacity versus pressure and temperature relationships. The factors leading to the loss of the pump volumetric efficiency during the four phases of the pump working cycle are theoretically analysed. Both differential and iterative methods are applied in the numerical solution of the model. The leakage model was validated against the measured leakage rates, and showed satisfactory results. A parametric study is carried out to analyze the effects the piston diameter has on the establishment process of the chamber pressure, the piston/cylinder interface leakage and the compression stroke. Results show that the impacts of the leakage, the compression stroke and the suction loss on the volumetric efficiency loss of the pump all increase with the nominal rail pressure.